Being Muslim in the Media Age: Muhammadiyah Students' Identity in the Midst of Celebrity Culture - Rina Sari Kusuma; Maryadi Maryadi; Palupi Palupi (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
This study explores how Muslim students at Muhammadiyah universities in Indonesia navigate their religious identity amid exposure to global celebrity culture. Using a mixed-methods approach, the research combines a quantitative survey of 194 undergraduate students with qualitative interviews of eight participants to analyze the influence of religiosity and celebrity culture on Muslim identity formation. Results indicate that religiosity significantly predicts the strength of Muslim identity, while celebrity culture has minimal direct impact. Interestingly, the study finds a positive correlation between religiosity and selective engagement in celebrity culture, suggesting that Muslim students actively curate media content in accordance with Islamic values. The qualitative findings further reveal strategies of identity negotiation, including selective media consumption, the use of social media as a hybrid space, and the role of family and campus communities in reinforcing religious boundaries. This research highlights the agency of Muhammadiyah students in critically responding to popular culture without compromising their Islamic identity, offering insights into the lived experiences of moderate Muslim youth in the media age.